La séduction et l’idéologie : sémantique, syntaxe, argumentation - Jean SZLAMOWICZ (E-REA)
This article aims to study seduction within the framework of discourse analysis as a special linguistic relation with an underlying aim. The seductive discourse is about making a stylistic effort that disguises the argument and makes it poetically appealing. Such is the basis of discursive seduction, connecting desire through the euphoria of words.The ‘desire’ of discourse is what comes into play when convincing becomes seducing: making a case cannot become effective if the words (their value, their connotations) don’t appeal to the desire to be convinced. In this instance, seduction is a rhetorical battle between logos and pathos.Studying the vocabulary of wine tasting, then other fields with more of an ideological stake, such as antisemitism, the article will show how political activism enlists seductive values as a strategy to win the audience over.The article will stress the role of incantatory importance of ‘word ethos’ and will develop the concept of hypostello, to mean a rhetorical strategy of hiding one’s intentions. Lexical and syntactical arsenal, axiology, metaphors, implicitness are but a few of the linguistic features that can be studied to determine the degree of seduction.